Answer:
x=3
Step-by-step explanation:
3(2x−4)−5(x−2)=1
Step 1: Simplify both sides of the equation.
3(2x−4)−5(x−2)=1
(3)(2x)+(3)(−4)+(−5)(x)+(−5)(−2)=1(Distribute)
6x+−12+−5x+10=1
(6x+−5x)+(−12+10)=1(Combine Like Terms)
x+−2=1
x−2=1
Step 2: Add 2 to both sides.
x−2+2=1+2
x=3
38 42 34 54
Step-by-step explanation:
7have the best mayonnaise bianco babi naive albino pig is this real or not be a posible and I am a great day for 53feet
Other Federalists claimed that the new government could not violate the people's rights because it only had limited powers. However, most state legislatures refused to ratify the Constitution without the Bill of Rights being added to the document.
12 not sure if it's true or not.